Development of Interactive Multimedia Based on Research of Hybridama Technology - El Fitro, Sulis; Bambang Sumitro, Sutiman; Lestari, Umie (Indonesian Journal of Science Learning (IJSL), 2022)
The ability to understand and apply the current methods of Biotecnology as hybridoma technology needs to be taught to students. But in conducting laboratory activities hybridoma technology in the classroom activities takes time and costs are relatively large. This study was conducted to generate instructional media for students based research. The purpose of this research is to produce learning multimedia of hybridoma technology in Biotechnology course. This study uses the ADDIE development model. The results of this research is based on the feasibility studies show that interactive multimedia on hybridoma technology feasible for use as a medium of learning. This feasibility in terms of the truth of the matter by matter experts in the amount of 88.96%, the feasibility of interactive multimedia as a medium of learning by expert instructional media by 75%, and students who have completed the course of biotechnology by 86.07%.